Kunjungan Studi Museum Berbasis Eksplorasi Multiaspek untuk Menggali Sisi Lain Dunia Permuseuman - Dadan Adi Kurniawan (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
Museums in Indonesia remain underutilized, as their educational function is frequently reduced to serving merely as media and sources for historical learning, while their broader institutional, cultural, and professional dimensions receive limited attention. This study addresses this partial approach by examining overlooked dimensions of museums and proposing alternative assignment designs, learning outputs, and assessment instruments for museum-based educational activities. Employing a qualitative descriptive approach, the study draws on direct observation and a literature review encompassing scholarly journals, books, theses, newspapers, YouTube content, and relevant articles. The findings demonstrate that museum exploration can extend beyond reconstructing historical narratives from collections to examining institutional origins, collection provenance and acquisition, conservation systems, professional expertise, exhibition practices, promotional strategies, and operational challenges. These dimensions provide opportunities for students to develop more comprehensive, critical, and contextual understandings of museums. The study concludes that educational visits to museums should adopt a multidimensional learning framework and incorporate assignments oriented toward innovative outputs, supported by appropriate assessment instruments, thereby transforming museum visits from passive observation into meaningful and productive learning experiences.